Brazilian Human Rights Foreign Policy Analysis In 2019-2022: Poliheuristic Theory - Nathania, Vania Zahra; Hanni, Ummu; Sya’bani, Muhammad Arya; Lekawael, Yonaso Henry; Advent, Nathanael (Kajian Hubungan Internasional, 2024)
This article aims to analyze Brazilian foreign policy in the field of human rights during the 2019-2022 administration of President Jair Bolsonaro using a poliheuristic theoretical framework. This research belongs to the category of qualitative research. Its data collection method is a literature study, and its data analysis method is a descriptive case study. The results show that the reason President Bolsonaro chose a foreign policy that focuses on human rights is to maintain Brazil's image, popularity, and close relations with other countries. President Bolsonaro applied the policy by participating in various UN efforts to solve HR-related issues. Brazilian foreign policy under President Bolsonaro has positive and negative consequences, but the former outweighs the latter. In conclusion, the application of poliheuristic theory worked well and helped the authors strengthen the understanding of decision-making related to Brazilian foreign policy in the field of human rights in the 2019-2022 period. Keywords: Brazilian Foreign Policy, Human Rights, Poliheuristic Theory, President Jair Bolsonaro.